Selective Covalent Modification of Layered Double Hydroxide Nanoparticles with Tripodal Ligands on Outer and Interlayer Surfaces - Muramatsu, Keisuke; Hayashi, Shiori; Kuroda, Yoshiyuki; Oka, Yuya; Wada, Hiroaki; Shimojima, Atsushi; Kuroda, Kazuyuki (Inorganic chemistry, 2020)
Layered double hydroxides (LDHs) have occupied an important place in the fields of catalysts, electrocatalysts, and fillers, and their applicability can be greatly enhanced by interlayer organic modifications. In contrast to general organic modification based on noncovalent modification using ionic organic species, this study has clarified in situ interlayer covalent modification of LDH nanoparticles (LDHNPs) with the tripodal ligand tris(hydroxymethyl)aminomethane (Tris-NH2). Interlayer-modified CoAl LDHNPs were obtained by a one-pot hydrothermal treatment of an aqueous solution containing metal salts and Tris-NH2 at 180 °C for 24 h. Tris-NH2 was covalently bonded on the interlayer surface of LDHNPs. Interlayer-modified NiAl LDHNPs were also similarly synthesized. Some comparative experiments under different conditions indicate that the important parameters for interlayer modification are the number of bonding sites per a modifier, the electronegativity of a constituent divalent metal element, and the concentration of a modifier; this is because these parameters affect the hydrolytic stability of alkoxy–metal bonds between a modifier and a layer of LDHNPs. The synthesis of interlayer-modified MgAl LDHNPs was achieved by adjusting these parameters. This achievement will enable new potential applications because modification of only the outer surface has been achieved until now. Interlayer-modified LDHNPs possessing CO3 2– in the interlayer space were delaminated into monolayers under ultrasonication in water. The proposed method provides a rational approach for interlayer modification and facile delamination of LDHNPs.